Prognostic factors at birth for stunting at 24 months of age in rural Indonesia - Endy Prawirohartono; Detty Nurdiati; Mohammad Hakimi (Indonesian Pediatric Society, 2016)
Background The problems of stunting are its high prevalence as well as the complexity of its risk factors. Identifying the modifiable prognostic factors at birth may reduce the shortterm as well as longterm effects of stunting in later life.Objective To estimate the influence of prognostic factors detected at birth for stunting at 24 months of age and the occurence of reversal of stunting at 24 months of age among children in a rural area of Indonesia.Methods Subjects (n=343) were born to mothers participating in a randomized controlled, double-blind, community-based study of vitamin A and/or zinc supplementation during pregnancy and followed from June 1998 to October 2000. The children were followed prospectively from birth until 2 years of age with monthly measurements of length from birth to 12 months, and again at 18 and 24 months. Data on potential prognostic factors detected at birth, i.e., maternal, child, and household facilities, were collected by trained field workers at home visits. The incidence and risk ratio were calculated to assess the influence of the possible prognostic factors detected at birth on stunting at 24 months of age among these children.Results Boys who were born prematurely had significantly higher risk of stunting at 24 months of age compared to girls born maturely. The incidences of stunting at 24 months of age according to gender, and gestational age were 33.9% boys vs. 22.5% girls (RR 1.80; 95%CI 1.06 to 3.09), and 33.3% premature vs. 27.6% mature (RR 7.11; 95%CI 2.07 to 24.48), respectively.Conclusion Boys who were born prematurely have significantly higher risk to become stunted at 24 months of age. The occurrence of reversal of stunting at 24 months of age is low.